Transplant administration—A survey of the roles and responsibilities of kidney and pancreas medical directors of US transplant centers. Issue 6 (27th April 2021) - Singh, Neeraj; Friedewald, John; Bloom, Roy; Dadhania, Darshana; Parsons, Ronald F.; Kaplan, Bruce; Samaniego, Millie; Qazi, Yasir; Doshi, Mona; McNatt, Gwen; Naseer, Muhammad Saad; Pesavento, Todd; et al.
Abstract: The current American Society of Transplantation (AST) accredited transplant fellowship programs in the United States provide no structured formal training in leadership and administration which is essential for successfully running a transplant program. We conducted a survey of medical directors of active adult kidney and kidney‐pancreas transplant programs in the United States about their demographics, training pathways, and roles and responsibilities. The survey was emailed to 183 medical directors, and 123 (67.2%) completed the survey. A majority of respondents were older than 50 years (61%), males (80%), and holding that position for more than 10 years (47%). Only 51% of current medical directors had taken that position after completing a one‐year transplant fellowship, and 58% took on the role with no prior administrative or leadership experience. The medical directors reported spending a median 50%–75% of time in clinical responsibilities, 25%–50% of time in administration, and 0%–25% time in research. The survey also captured various administrative roles of medical directors vis‐à‐vis other transplant leaders. The study, designed to be the starting point of an improvement initiative of the AST, provided important insight into the demographics, training pathways, roles and responsibilities, job satisfaction, education needs, and training gaps of current medical directors.